Traditional schedule - Zucker, Alan (Henry Stewart Talks, 2025)
Create schedule, Project scheduling options, Milestone, Identify activities, Arrange tasks, Deliverables vs. activities, Gantt chart, Critical path, Float or slack, Choosing project tools